Standardized counting of circulating platelet microparticles using currently available flow cytometers and scatter‐based triggering: Forward or side scatter?. (11th May 2015) - Poncelet, P.; Robert, S.; Bouriche, T.; Bez, J.; Lacroix, R.; Dignat‐George, F.
Abstract: Clinical determination of MP counts using flow cytometry has not been fully accepted yet due to the lack of standardization protocols. In the past 5 years, we have proposed two versions of a method with reproducible PMP counts in plasma samples. Both methods use forward scatter (FSC)–based threshold set with reference beads of appropriate sizes; first using 0.5 µm beads and later with 0.3 µm beads. Both systems provide reproducible PMP counts. However, this technique works only with some of currently used commercial flow cytometers. Instruments with limited resolution or generating heterogeneous FSC signals are excluded. Such performances are incompatible with the required interinstrument standardization. Here we show that (i) flow cytometers with sub‐optimal FSC capabilities generally have higher SSC resolution and background rejection capacity, and (ii) that the same biological entities, "dim and bright PMP, " both can be counted using alternative strategies, either as previously described, based on FSC measurements, or as presented here, based on SSC detection. The critical element in the standardization protocol is the use of different sizes of reference beads. This study was designed to permit simultaneous access to both FSC‐ and SSC‐optimized platforms. A new range of about 0.17–0.6 µm eq. (µm‐equivalents) is proposed for an alternative SSC–based MP gate generating the same PMP counts as those obtained in the previously proposed 0.3–1 µm eq. FSC–based MP gate. The two equivalent standardization options reconcile intrinsically different scattering behaviors between SSC‐ and FCS ‐ triggered instruments and open the opportunity for multicenter studies in the future. © 2015 International Society for Advancement of Cytometry